Solving of the Quadratic Fractional Programming Problems by a Modified Symmetric Fuzzy Approach - A. Nawkhass, Maher; Nejmaddin A. Sulaiman, (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The aims of the paper are to present a modified symmetric fuzzy approach to find the best workable compromise solution for quadratic fractional programming problems (QFPP) with fuzzy crisp in both the objective functions and the constraints. We introduced a modified symmetric fuzzy by proposing a procedure, that starts first by converting the quadratic fractional programming problems that exist in the objective functions to crisp numbers and then converts the linear function that exists in the constraints to crisp numbers. After that, we applied the fuzzy approach to determine the optimal solution for our quadratic fractional programming problem which is supported theoretically and practically. The computer application for the algorithm was tested, and finally compared modified symmetric fuzzy approach with the modified simplex approach which is shown in the table 1. Finally, the procedures of numeric results in the paper indicate that modified symmetric fuzzy approach is reliable and saves valuable time.